2021
DOI: 10.1088/1755-1315/677/5/052041
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the main mechanical characteristics of plastics for three-dimensional printing of machine parts models

Abstract: Today, new methods of manufacturing complex parts using three-dimensional printing are being introduced in engineering, including in the mechanical engineering of agricultural machinery. This technique is also used in the design of agricultural machinery at the stage of physical modeling of their structures to determine certain properties of the product as a whole and its individual parts (details) on the corresponding models. Physical modeling is used when it is difficult to perform full-scale tests of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…At the same time, from an economic point of view, it is important to systematically reduce energy costs to ensure the required temperature regime throughout the year when the values of outdoor air temperature and natural solar radiation vary in a wide range. In scientific works devoted to the influence of air temperature in the production room on the human body, it is indicated that a decrease in temperature by 4 °C is considered sharp for the human body [19][20][21][22][23][24][25][26][27][28][29][30], but at the same time it can significantly reduce heating costs. In addition, a decrease in temperature from the normalized values during vaccination and the fight against viral seasonal diseases can lead to a decrease in workers' immunity.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, from an economic point of view, it is important to systematically reduce energy costs to ensure the required temperature regime throughout the year when the values of outdoor air temperature and natural solar radiation vary in a wide range. In scientific works devoted to the influence of air temperature in the production room on the human body, it is indicated that a decrease in temperature by 4 °C is considered sharp for the human body [19][20][21][22][23][24][25][26][27][28][29][30], but at the same time it can significantly reduce heating costs. In addition, a decrease in temperature from the normalized values during vaccination and the fight against viral seasonal diseases can lead to a decrease in workers' immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Для определения механических свойств пластика, из которого выполнена модель опорноцентрирующего устройства, и построения диаграммы растяжения необходимо провести испытания на разрыв образцов из пластика PLA [16,17].…”
Section: рис 6 граничные условия применяемые к опорноцентрирующему ус...unclassified
“…In addition, the movement of the material along the x axis will be neglected by u ≈ 0. With regard to the problem under study on a symmetric integration interval, in the case of a limited solution at both ends of the segment [-t, +t], we have [4][5][6][7][8][9][10][11][12][13][14][15]:…”
Section: Development Of a Mathematical Modelmentioning
confidence: 99%
“…If in expression (7) the symbol "tends" to be replaced by -"equal", it will become a condition of equal strength when the contact normal stresses are distributed evenly over the wear surface of the blade [10], while the line of action is equivalent to the intensity of stresses…”
Section: Optimization Of the Blade Positionmentioning
confidence: 99%